Effectiveness of the Posyandu Program on the Nutritional Status of Toddlers in Indonesia - Deandra Ceacilia Gabriela (International Journal of Nursing and Midwifery Research, 2026)
Toddler nutrition remains a significant public health concern, particularly in developing countries such as Indonesia, where problems such as underweight, stunting, and wasting can affect children’s growth and development. Community-based health services play an important role in addressing these issues, one of which is the Posyandu (Integrated Health Service Post), which provides services such as growth monitoring, immunization, nutrition counseling, and supplementary feeding for mothers and children. This study aimed to analyze the effectiveness of the Posyandu program on the nutritional status of toddlers. The research employed a quantitative cross-sectional design conducted in several Posyandu units within the study area. The study population consisted of toddlers aged 0-59 months and their mothers, from which a sample was selected using a simple random sampling technique. Data were collected through anthropometric measurements, observation, and structured questionnaires. The nutritional status of toddlers was assessed using indicators such as weight-for-age, height-for-age, and weight-for-height. Data analysis was performed using descriptive statistics and the Chi-square test to determine the relationship between participation in Posyandu activities and toddler nutritional status. The results showed that the majority of toddlers who regularly attended Posyandu had normal nutritional status, while those who attended irregularly were more likely to experience nutritional problems. Statistical analysis also indicated a significant relationship between Posyandu participation and toddler nutritional status. In conclusion, the Posyandu program is an effective community-based health strategy for monitoring child growth and improving the nutritional status of toddlers. Strengthening community participation and enhancing the quality of Posyandu services are essential to support better child health outcomes.